Bacterial profile of blood stream infections and their antibiograms - Kante, Meenakshi; P, Muni Lakshmi; P, Sreenivasulu Reddy (International Journal of Research in Medical Sciences, 2017)
Background: Blood culture provides essential information for the evaluation of a variety of diseases like endocarditis, pneumonia, and pyrexia of unknown origin particularly, in patients with suspected sepsis. Septicaemia is one of the leading causes of neonatal mortality along with perinatal hypoxia. Objectives: To study the bacterial flora of blood stream infections in adults & pediatric patients including neonates. To study the risk factors and duration of incubation for obtaining positive cultures. To study their antibiotic resistant pattern and compare results with those of other investigators in this field. Methods: This prospective study was conducted in the department of microbiology, Narayana medical college and hospital, Nellore over a period of six months, from March 2014 to September 2014. During the six months period, 200 samples received from various departments were processed and relevant findings were noted. Results: Out of 200 blood samples growth was obtained in 34 samples (17%). Among them Gram positive bacteria were 11 (5.5%). Gram negative bacilli were 23 (11.6%). Among the gram positive bacteria maximum resistance was seen with methicillin and imipenum. No resistance was seen with vancomycin and erythromycin. Most of gram negative bacilli were multidrug resistant. Maximum resistance was seen with piperacillin, amikacin, ceftizoxime and amoxyclav. Conclusion: Early diagnosis & appropriate treatment of bacterial infections can make difference between life & death. It would reduce mortality from septicaemia, reduce time & improve patient management.